2018
DOI: 10.1016/j.ijnurstu.2018.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to prevent and reduce the impact of musculoskeletal injuries among nurses: A systematic review

Abstract: There is an absence of high quality published studies investigating interventions to protect nurses from musculoskeletal injuries and pain. Further research (including randomised controlled trials) is needed to identify interventions that may reduce the high rates of injury and pain among nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
92
4
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(102 citation statements)
references
References 54 publications
2
92
4
4
Order By: Relevance
“…They also exerted devastating effects on the personnel's health, quality of life, and job satisfaction and could lead to https://doi.org/10.1016/j.cegh.2020.03.019 Received 30 January 2020; Received in revised form 7 March 2020; Accepted 19 March 2020 loss of workdays. 12,13 Studies in the Europe demonstrated that almost 40 million workers (more than 30%) suffered from these disorders, accounting for 0.5-2% of the European Union's Gross Domestic Product (GDP). 2 Despite the high prevalence of MSDs in communities, healthcare personnel are faced more with these problems.…”
Section: Introductionmentioning
confidence: 99%
“…They also exerted devastating effects on the personnel's health, quality of life, and job satisfaction and could lead to https://doi.org/10.1016/j.cegh.2020.03.019 Received 30 January 2020; Received in revised form 7 March 2020; Accepted 19 March 2020 loss of workdays. 12,13 Studies in the Europe demonstrated that almost 40 million workers (more than 30%) suffered from these disorders, accounting for 0.5-2% of the European Union's Gross Domestic Product (GDP). 2 Despite the high prevalence of MSDs in communities, healthcare personnel are faced more with these problems.…”
Section: Introductionmentioning
confidence: 99%
“…To avoid the risk of LBP in nurses, training or education, no-lift policies and several devices to assist patient transfers, including battery-powered lifts, sliding boards, and ceilingbased patient lifts, have been attempted [10][11][12]. However, these interventions have not been established to prevent LBP because there is no strong evidence for their efficacy according to systematic reviews [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of low back pain has been estimated to be 15-45% among the general population worldwide. Besides, it has been estimated that approximately 70-80% of the general population experience a back problem some time in their lives (4,7,8). The prevalence of low back pain, as the most important musculoskeletal disorder, has been reported to be 30-60% among nurses (9).…”
Section: Introductionmentioning
confidence: 99%